2019
DOI: 10.1016/j.fertnstert.2019.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Euploidy rates between cycles triggered with gonadotropin-releasing hormone agonist and human chorionic gonadotropin

Abstract: Objective: To evaluate differences in euploidy rates between IVF cycles triggered with either GnRH agonist (GnRHa) or hCG. Design: Retrospective cohort study. Setting: University-affiliated fertility center. Patient(s): A total of 366 patients performing 539 IVF cycles utilizing preimplantation genetic testing for aneuploidy (PGT-A). Intervention(s): Gonadotropin-releasing hormone agonist or hCG trigger of oocyte maturation during IVF cycles. Main Outcome Measure(s): Rate of euploid embryos. Result(s): Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…In our study, women who attained more euploidy blastocysts was found to have increased serum AMH concentration. This was in line with ndings by Antonio La Marca et al which indicates that independently from age, increased ovarian reserve is in accordance with an increased rate of embryo aneuploidy [5,18,19]. In addition,This conclusion could explain that after a unilateral oophorectomy (reduced ovarian reserve) in female mice, the number of aneuploidy (low-quality oocytes) will rise earlier than expected [20].…”
Section: Amh and Number Of Euploidy Blastocystssupporting
confidence: 89%
“…In our study, women who attained more euploidy blastocysts was found to have increased serum AMH concentration. This was in line with ndings by Antonio La Marca et al which indicates that independently from age, increased ovarian reserve is in accordance with an increased rate of embryo aneuploidy [5,18,19]. In addition,This conclusion could explain that after a unilateral oophorectomy (reduced ovarian reserve) in female mice, the number of aneuploidy (low-quality oocytes) will rise earlier than expected [20].…”
Section: Amh and Number Of Euploidy Blastocystssupporting
confidence: 89%
“…As observed previously, the surge of gonadotrophins elicited by a bolus of GnRHa differs from that of the natural midcycle of gonadotrophins in duration and profile. It has also been shown that the elicited flare of LH as well as FSH resembles the natural midcycle surge of gonadotrophins and was found to effectively stimulate final oocyte maturation and ovulation (10), leading to the development of competent embryos as recently demonstrated in PGT-A cycles (11). Moreover, studies in oocyte donors (12) and oncologic fertility-preservation patients (13,14) demonstrated a significant increase in MII oocytes and the number of good-quality embryos in GnRHa-triggered cycles as compared with hCGtriggered cycles.…”
Section: Gnrha Trigger-improving Oocyte Yield and Embryo Competence?mentioning
confidence: 79%
“…Although we cannot provide results for embryo quality according to the trigger method, the reproductive outcomes of oocytes treated with a dual-trigger approach do not seem to be compromised. Thorne et al [20] recently reported that the embryo aneuploidy rate was similar in patients stimulated with a GnRH agonist trigger and patients administered an hCG trigger. Embryo development and quality appear to be unaffected in GnRH agonist trigger cycles [21].…”
Section: Discussionmentioning
confidence: 96%